Fabrication and characterization of Li4SiO4 pebbles by extrusion spherodization technique: Effects of three different binders. Issue 3 (15th February 2019) - Jaya Rao, G.; Mazumder, R.; Dixit, D.; Ghoroi, C.; Bhattacharyya, S.; Chaudhuri, P.
Abstract: The present report demonstrates the effects of three different binders on fabrication of Li4 SiO4 pebbles by extrusion-spherodization technique. It is found that the nature of binders, concentrations and moisture content have significant effect on the density, sphericity, grain size and crush load of the Li4 SiO4 pebbles. Different viscosity grade binders namely PVA, PVP and guargum have been explored for the fabrication of pebbles. XRD, FESEM, BET, Inverse gas chromatography, pebble crush load tester are used to study different properties. It has been observed that the pebbles fabricated with 6 wt% PVP show the desired properties [appreciable density (85%), smaller grain size (<8 µm), good sphericity (0.98) and notable crush load (17 N)] when compared with the other two binders. Surface energy and microstructure of the green aggregates provide some comprehensive information for achieving desired properties in PVP derived pebbles. The effects of the sintering temperature on the different properties have also been studied.